Active Offer - A culture of respect, a culture of excellence - Commissariat aux langues officielles (2017)
pages: 19

L’offre active une culture de respect, une culture d’excellence : guide complet - Commissariat aux langues officielles (2017)
fs-ref-orig: Commissariat aux langues officielles. (2017). L’offre active une culture de respect, une culture d’excellence : guide complet. fs-code-orig: Commissariat aux langues officielles-2017.

Démonstration de la valeur ajoutée de la collecte de l'identité linguistique [webinaire] - Desaulniers, Jacinthe; Manseau, Jasmin (2017)

Des outils efficaces pour colliger des informations sur la capacité du système de santé à offrir des services en français: Démonstration en Ontario. [webinaire] - Desaulniers, Jacinthe; Pagé, Jean-Francois (2017)

A guide for Planning and Providing Francophone Long-term Care Services - Learning from Pavillon Omer Deslauriers (POD) at Bendale Acres and Other Franch Language Health Services for Seniors in Canada - FRENCH HEALTH NETWORK OF CENTRAL SOUTHWESTERN ONTARIO (2017)
pages: 92

Démonstration d’une méthodologie mettant à profit les modèles de Rasch : l’exemple d’une échelle de la mesure de l’offre active de services en français. - Grondin, Julie; Dionne, Éric; Savard, Jacinthe; Casimiro, Lynn (Regards actuels et prospectifs sur l’évaluation des apprentissages complexes en éducation dans le domaine de la santé, 2017)

Les bienfaits de la socialisation au programme de jour du Centre de services Guigues (CSG) sur la santé des personnes âges francophones ayant vécu l'isolement ou la solitude dans la région d'Ottawa - Kajuka, Dale (Université Laurentienne, 2017)
fs-ref-orig: Kajuka, D. (2017). Les bienfaits de la socialisation au programme de jour du Centre de services Guigues (CSG) sur la santé des personnes âges francophones ayant vécu l'isolement ou la solitude dans la région d'Ottawa [mémoire de maîtrise, Université Laurentienne]. Zone UL. https://zone.biblio.laurentian.ca/handle/10219/2836 fs-code-orig: Kajuka-2017

An evaluation of FrancoForme: A case-managed home-based primary and secondary cardiovascular disease prevention program for French-speaking Canadians - Prince, Stephanie. A.; Laflamme, Marc; Harris, Jennifer; Tulloch, Heather E.; de Margerie, Michele (Journal of cardiopulmonary rehabilitation and prevention, 2017)
Purpose: Cardiovascular disease (CVD) is the leading cause of mortality globally. Telephone-delivered interventions targeting cardiovascular risk factors are gaining popularity. This study is an evaluation of FrancoForme, a cardiovascular risk factor reduction program for the primary and secondary prevention of CVD among French-speaking patients of Eastern Ontario. Methods: This study reports on changes in cardiovascular risk factors, weekly exercise levels, and psychosocial characteristics including anxiety, depression, and quality of life upon program completion (3 months) and at 1 year after the start of the program. Repeated-measures analysis of variance was used to compare changes in outcomes between primary prevention risk groups (low, moderate, and high risk for CVD) and the secondary prevention group (ie, cardiac rehabilitation) at baseline, 3 months and 12 months. Results: A total of 762 patients enrolled in FrancoForme between 2008 and 2015. At 3 months, all program completers (n = 507) experienced significant reductions for all cardiovascular risk factors except diastolic blood pressure. Minutes of self-reported exercise increased significantly by an average 90 minutes per week and all psychosocial variables improved. Significant group effects were observed across several risk factors. Among 12-month responders (n = 240), exercise, high-density lipoproteins, triglycerides, cholesterol, and all psychosocial variables were improved over baseline results. Conclusions: FrancoForme is unique in targeting both the primary and secondary prevention of CVD and removes several of the barriers to participating in a conventional CVD prevention program for French-speaking patients. FrancoForme is successful, receiving high satisfaction rates and resulting in significant improvements in cardiovascular risk factors, exercise, anxiety, and depression, as well as quality of life.

Behaviours demonstrating active offer: Identification, measurement, and determinants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
In this chapter, we present the behaviours we have identified encouraging and demonstrating the active offer (AO) of social services and health care in French in minority settings, how we measured them, and how we used these measurements to identify the determinants of AO. We will discuss the tools we developed to measure individual AO behaviours, individual perception of organizational support for AO, and personal characteristics that influence AO behaviours (determinants). Various quantitative methods were used to reach our objectives. The results demonstrate that organizational support is the most important determinant of individual AO behaviours. Once controlled for, additional factors included three personal characteristics that increase propensity to demonstrate AO behaviour: education about AO, affirmation of Francophone identity, and competency in French. The sense of competency in English, on the other hand, has a negative association with AO of French-language service. A better understanding of these determinants enables us to refine our strategies to improve the awareness and education of future health and social service professionals on AO. Key Words: active offer behaviours, measurement, determinants, organizational support, individual behaviours, quantitative research.
Chapter 12

Les comportements favorables à l’offre active, leur mesure et leurs déterminants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce chapitre, nous présenterons comment nous avons répertorié des comportements favorables à une offre active (OA) de services sociaux et de santé en français en contexte minoritaire, comment nous les avons mesurés et comment nous avons utilisé ces mesures pour déceler des déterminants de l’OA. Nous présentons en détail l’élaboration des outils qui ont servi à mesurer les comportements d’OA, le soutien organisationnel perçu envers l’OA et les caractéristiques personnelles qui peuvent influer sur les comportements d’OA (déterminants). Diverses méthodes quantitatives ont été utilisées pour atteindre ces objectifs. Les résultats obtenus démontrent la présence d’un fort lien entre le soutien organisationnel perçu et les comportements individuels d’OA. À soutien organisationnel égal, les caractéristiques individuelles associées à une plus grande propension à démontrer des comportements d’OA incluent une formation sur l’OA, l’affirmation identitaire et la compétence en français. Le sentiment de compétence en anglais est quant à lui associé négativement aux comportements individuels d’OA de services en français. Une meilleure connaissance de ces déterminants permet de raffiner les stratégies de sensibilisation et d’éducation des futurs professionnels de la santé et des services sociaux envers l’OA. Mots-clés : comportements d’offre active, mesure, déterminants, soutien organisationnel, comportements individuels, recherche quantitative.
Chapitre 12

Active Offer of French-Language Health Services for Francophone and Acadian Minority Communities in Canada - Joint position statement - Société Santé en français (2017)
pages: 10

L'offre active des services de santé en français dans les communautés francophones et acadienne en situation minoritaire au Canada - Énoncé de position commune - Société Santé en français (2017)
pages: 10